Overcrowding in emergency departments: A review of strategies to decrease future challenges - Yarmohammadian, Mohammad H (J Res Med Sci, 2017)
Emergency departments (EDs) are the most challenging ward with respect to patient delay. The goal of this study is to present strategies that have proven to reduce delay and overcrowding in EDs. In this review article, initial electronic database search resulted in a total of 1006 articles. Thirty articles were included after reviewing full texts. Inclusion criteria were assessments of real patient flows and implementing strategies inside the hospitals. In this study, we discussed strategies of team triage, point-of-care testing, ideal ED patient journey models, streaming, and fast track. Patients might be directed to different streaming channels depending on clinical status and required practitioners. The most comprehensive strategy is ideal ED patient journey models, in which ten interrelated substrategies are provided. ED leaders should apply strategies that provide a continuous care process without deeply depending on external services.